2020
DOI: 10.1177/0885328220933781
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of bone cements impregnated with selenium nanoparticles stabilized by phosphatidylcholine (PC) for application in bone

Abstract: One of the most common prophylactic techniques to solve prosthetic joint infection (PJI) is incorporation of antibiotics into acrylic bone cement to prevent bacterial colonization and proliferation by providing local antibiotic delivery directly at the implant site. Further, there has been a significant concern over the efficacy of commonly used antibiotics within bone cement due to the rise in multi-drug resistant (MDR) microorganisms. Selenium is an essential trace element that has multiple beneficial effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Through these results, it was confirmed that SeNPs at a concentration of 5–10 μg/mL promote the differentiation of MC3T3-E1 cells. In addition to previous studies reporting improved cell adhesion and osteoblast function [ 36 ], SeNPs protect against ROS-induced damage and are related to cell growth and differentiation regulation [ 67 , 68 , 69 ], confirming that they also affect the differentiation of cells.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Through these results, it was confirmed that SeNPs at a concentration of 5–10 μg/mL promote the differentiation of MC3T3-E1 cells. In addition to previous studies reporting improved cell adhesion and osteoblast function [ 36 ], SeNPs protect against ROS-induced damage and are related to cell growth and differentiation regulation [ 67 , 68 , 69 ], confirming that they also affect the differentiation of cells.…”
Section: Resultssupporting
confidence: 64%
“…Selenium is one of the important trace elements in the human body that regulates various physiological functions, such as antioxidant behavior, anti-inflammatory effects, and immunity functions [ 36 , 37 , 38 ]. Selenium plays a role in relieving oxidative stress in fibroblasts subjected to heat shock [ 39 ], inhibits the cell cycle, and induces cytotoxicity and apoptosis in carcinogenic cell lines of the colon, breast, lung, or prostate [ 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the relatively complex material preparation and characterization process, a limited number of publications have reported the use of selenium for 3D scaffolds. Most studies focused on the incorporation of selenium into ceramic, polymeric, and metallic nanoparticles, as well as a coating of metallic substrate [122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137]. These studies suggested that selenium is an effective functional material that can be used to treat bone cancer problems without affecting normal cells, also promoting bone regeneration, which is related to its antioxidant and prooxidant properties.…”
Section: Scaffolds With Advanced Functional Materialsmentioning
confidence: 99%
“…Selenium is one of the essential trace elements that regulate various physiological functions, including anti-inflammatory effects and immune functions [ 28 , 29 , 30 , 31 ], and is also well known to play an essential role in regulating ROS levels [ 32 , 33 , 34 , 35 ]. Selenium has been reported to protect fibroblasts from oxidative stress [ 36 ] and apoptosis [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%